Leveraging Instagram for Public Service Communication: A Case Study of LRT Jabodebek - Yulianti Fajar Wulandari; Putri Nabila Suherman; Ali Imron Hamid; Yan Bastian (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates how Instagram serves as a public service communication tool for LRT Jabodebek, a new urban rail transit system in Greater Jakarta, Indonesia. The research aimed to analyze the platform’s role in disseminating information, engaging users, and improving service delivery. Using a descriptive qualitative method, non-participant observation and documentation analysis were conducted on the official Instagram account @lrt_jabodebek between April and June 2025. From 461 posts, eight were selected based on engagement metrics, including schedule updates, safety campaigns, ridership milestones, and feedback responses. Findings reveal that Instagram enhanced service through real-time updates, transparency, and public education. The account frequently shared schedules, addressed complaints, and promoted commuter etiquette and safety systems. Increased engagement correlated with higher ridership from March to May 2025. The study concludes Instagram is now a central communication channel for urban transport, recommending content diversification, faster responses, and cross-platform integration for greater effectiveness.